Optimal taxation and congestion externalities in a model of household time allocation - Nielsen, Jens Erik; Pilegaard, Ninette (Proceedings from the Annual Transport Conference at Aalborg University, 2005)
When wanting to solve the externality problem in the transport sector the tax system is an available instrument and the optimal tax system has been analyzed extensively. Unfortunately many of the approaches fail to take account of the insights pointed out in Becker (1965) that the allocation of household time is important for the characterization of household behavior. Since transports main characteristic is that it consumes time this insight should be applied to the transport sector. Recent papers have analyzed the optimal tax system in this setup (Kleven (2004), Nielsen and Pilegaard (2004)) in situations with and without atmospheric externalities. It was shown that the inclusion of household time changes the formulas for optimal taxation and these changes has direct policy implications. If the Becker setup is to be applied to the transport sector an analysis of the optimal tax system in the presence of congestion externalities is needed. This lack of insight is the focus of the present paper. The purpose here is to implement congestion type externalities in a Becker-like setup which explicitly models the use of household time. The paper demonstrates the strength of the Becker approach since existing tax results emerge as special cases in the present setup. The formulas derived for the optimal tax is a valuable guidance when designing the tax system in the transport sector.